2018
DOI: 10.1080/09593985.2018.1442540
|View full text |Cite
|
Sign up to set email alerts
|

Recovering from provoked vestibulodynia: Experiences from encounters with somatocognitive therapy

Abstract: Although provoked vestibulodynia (PVD) represents a significant challenge for many young women in the Western world, little is known about how these women experience therapeutic efforts. The aim of this paper is to enhance our knowledge of the way that the therapeutic process is experienced by women with PVD undergoing somatocognitive therapy (SCT). The study enhances insight into this recently developed therapy through a detailed description of the physiotherapy approach. The empirical data are based on inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Studies focused on a single class of intervention (ie, pharmacological, psychological, and physical modalities) were separated out into multiple publications given the volume of studies and are reported elsewhere. 13 Studies of somatocognitive therapy 14,15 are described in the psychological therapies publication rather than here, as the emphasis of these interventions is on developing conscious bodily awareness and cognitive retraining to change movement and function. Somatocognitive therapy is a unique, psychologically oriented intervention delivered by a group of physiotherapists in Norway.…”
Section: Methodsmentioning
confidence: 99%
“…Studies focused on a single class of intervention (ie, pharmacological, psychological, and physical modalities) were separated out into multiple publications given the volume of studies and are reported elsewhere. 13 Studies of somatocognitive therapy 14,15 are described in the psychological therapies publication rather than here, as the emphasis of these interventions is on developing conscious bodily awareness and cognitive retraining to change movement and function. Somatocognitive therapy is a unique, psychologically oriented intervention delivered by a group of physiotherapists in Norway.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, SCT has been developed to treat women with PVD [ 22 24 , 43 , 44 ]. SCT is a multimodal physiotherapy treatment approach previously shown to be effective in the treatment of chronic pelvic pain [ 19 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…48 In Table 5, the online ACT program, 17 manual perineal rehabilitation with lidocaine 54 and somatocognitive therapy 56 showed improvements in sexuality. The qualitative study with somatocognitive therapy enabled women to develop a new relationship with their vulvas, so that this body area no longer seems distant or threatening 62 ; positive interference in sexual functioning may be related to this improvement. 63…”
Section: Sexual Functionmentioning
confidence: 99%